1978
DOI: 10.1159/000128020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Xanthine Oxidase Inhibitor on Adenine Nucleotide Degradation in Hemorrhagic Shock

Abstract: Biochemical effects of treatment with a xanthine oxidase inhibitor (allopurinol) were investigated in an experimental hemorrhagic shock procedure. Allopurinol pretreatment abolished the increase in plasma uric acid which occurs in untreated dogs during hemorrhagic hypotension and resulted in a much lesser increase in plasma allantoin. The pancreatic, liver and duodenal adenosine triphosphate (ATP) and total adenine nucleotides of untreated dogs were severely reduced, while those of allopurinol-pretreated dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…The lack of change in myocardial adenine nucleotides, in response to these procedures does, however, contrast with that of other tissues. Although no other measurements of nonmyocardial adenine nucleotides were made in the studies described in this paper, in the liver, kidney and intestine, under similar conditions, the adenine nucleotide content is markedly reduced, and this is prevented by allopurinol pretreatment (Chaudry et al, 1974;Hopkins et al, 1975;Cunningham & Keaveny, 1978). It therefore appears that there is some heterogeneity in the response of different tissues to haemorrhagic shock and reperfusion, and in the myocardium, at least, this does not involve changes in adenine nucleotide.…”
Section: Discussionmentioning
confidence: 65%
“…The lack of change in myocardial adenine nucleotides, in response to these procedures does, however, contrast with that of other tissues. Although no other measurements of nonmyocardial adenine nucleotides were made in the studies described in this paper, in the liver, kidney and intestine, under similar conditions, the adenine nucleotide content is markedly reduced, and this is prevented by allopurinol pretreatment (Chaudry et al, 1974;Hopkins et al, 1975;Cunningham & Keaveny, 1978). It therefore appears that there is some heterogeneity in the response of different tissues to haemorrhagic shock and reperfusion, and in the myocardium, at least, this does not involve changes in adenine nucleotide.…”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, it would be anticipated that the content of cellular high energy phosphates might decrease, leading to an increase in the serum concentration of hypoxanthine -a degradation product of intracellular nucleotides. The concentration of serum hypoxanthine is known to correlate inversely with the cellular energy state (the cellular high energy phosphate content) [23][24][25]. A similar ATP-depletion theory for the pathogenic mechanism of rhabdomyolysis in severely phosphate depleted patients has previously been proposed by Rowland [26].…”
Section: Discussionmentioning
confidence: 95%
“…This aberrant metabolic process damages the cell either through the generation of cytotoxic radicals (2 7 and H202) from xanthine oxidase, or through a depletion of cellular purine stores, which impairs the ability of the cells to maintain sufficient phosphate compounds for cell membrane integrity. Allopurinol, a xanthine oxidase inhibitor, has been repeatedly shown to increase the survival period in haemorrhagic shock in dogs (Crowell et al, 1969;Cunningham & Keaveny, 1978;Chambers et al, 1985) and rats (Cederna et al, 1990), and superoxide dismutase has been found to ameliorate splanchnic artery occlusion shock in rats (Bitterman et al, 1988). Favourable results have also been obtained with the spin-trapping agent PBN in a traumatic model of shock in rats (Novelli, 1992).…”
Section: Discussionmentioning
confidence: 99%